THE IMPORTANCE OF THE RESISTANCE INDEX IN PREDICTING THE DEVELOPMENT OF CHRONIC KIDNEY DISEASE - Shakhlo A. Orzikulova (Central Asian Journal of Medicine, 2024)
Purpose of the study: to identify the resistance index in predicting the development of chronic kidney disease in patients with metabolic syndrome. Material and methods of the study. Body mass index (BMI), complete blood count, blood biochemistry, albuminuria level and glomerular filtration rate (GFR), and renal artery Doppler ultrasound were determined in 205 patients with metabolic syndrome. Results: a model for predicting the development of chronic kidney disease was created for the early diagnosis of kidney damage in patients with metabolic syndrome, taking into account albuminuria, glomerular filtration rate and resistance index. Conclusion: Doppler ultrasound of the renal arteries is recommended for patients with impaired glucose tolerance.